Effectiveness of Zakat as an Instrument for Civil Society Empowerment:A Systematic Review of Mustahik Consumption Behavior - Anas Tania Januari; Rihas Tukha (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2026)
Zakat is a fundamental instrument of Islamic economics with significant potential for poverty alleviation and community empowerment. Despite the growing body of research on zakat’s social-economic roles, there remains a research gap regarding the specific mechanisms through which zakat programs influence the consumption behavior transformation of mustahik across diverse Muslim-majority contexts. This research aims to analyze the effectiveness of zakat as an instrument for civil society empowerment in changing mustahik consumption behavior through a systematic literature review. It also identifies key factors influencing the success of zakat programs in establishing more productive and sustainable consumption patterns. The Systematic Literature Review (SLR) method with PRISMA protocol was applied. Data were sourced from articles published during 2013–2023 in international databases including Emerald Insight, Google Scholar, and DOAJ. Of 47 articles initially identified, 11 were selected through rigorous inclusion criteria for in-depth thematic analysis. The findings reveal that zakat significantly impacts mustahik consumption behavior by shifting patterns from consumptive to productive. Key success factors include program quality, financial literacy, sustained mentoring, institutional governance, and local cultural context. This study contributes a novel synthesis framework linking zakat governance dimensions with behavioral transformation outcomes, providing evidence-based policy recommendations for zakat institutions.